A Doubly Interpenetrated Cu(II)‐based Metal‐Organic Framework as a Heterogeneous Catalyst for the ipso‐Hydroxylation of Arylboronic Acids. Issue 8 (4th January 2023) - Rani, Pooja; Heena; Pundir, Niharika; Gauri; Husain, Ahmad; Bhasin, K. K.; Kumar, Girijesh
Abstract: A doubly interpenetrated Cu(II)‐organic framework with formula [Cu2 (L )2 (4, 4′‐bpdc)2 (H2 O)2 ⋅ 8H2 O ⋅ CH3 OH]α (1 ) (where, L =N 2, N 6 ‐di(pyridin‐4‐yl)naphthalene‐2, 6‐dicarboxamide and 4, 4′‐bpdc=[1, 1′‐biphenyl]‐4, 4′‐dicarboxylate ion) has been synthesized and characterized with the help of several spectroscopic and analytical techniques including single crystal X‐ray analysis. A single crystal X‐ray analysis reveals that 1 exhibit interpenetrated two‐dimensional sheet‐like structure containing elongated channels of cross‐section 11.09×31.22 Å 2 along the a ‐axis. Finally, 1 has been exploited as a heterogeneous catalyst for the ipso ‐hydroxylation of arylboronic acids yielding up to 99 % of the respective phenolic product. Importantly, the catalyst can be reused for five successive cycles without having a significant loss in its catalytic efficiency. Abstract : A doubly interpenetrated Cu(II)‐based MOF 1 has been synthesized, structurally characterized and exploited as a heterogeneous catalyst for the ipso ‐hydroxylation of arylboronic acids.